Smart Tourism and Environmental Sustainability: A Descriptive and Analytical Case Study of Saudi Arabia - Hassan, Ashraf Fawzy (Journal of engineering sciences and information technology, 2025)
The study explores the role of smart tourism in promoting environmental sustainability by leveraging modern technologies to reduce environmental impact and improve destination management. It emphasizes the need to develop infrastructure and regulations to advance this sustainable approach.Objectives: The study aims to explore the integration between smart tourism and environmental sustainability by analyzing its technologies and role in reducing environmental impact, evaluating global experiences, and proposing practical mechanisms to support the achievement of sustainable development goals. It also addresses challenges and ways to enhance environmentally responsible behavior through smart technologies.Methods: The research adopts a descriptive-analytical approach to examine smart tourism and its environmental impact by reviewing relevant literature and international case studies, analyzing quantitative and qualitative data, and comparing traditional and smart models to provide a comprehensive vision that supports environmental sustainability.Results: The study’s findings confirm that smart tourism effectively contributes to environmental sustainability by enhancing resource efficiency, enabling digital monitoring of environmental impacts, and promoting responsible tourist behavior. It also highlights the importance of supportive legislation and global experiences in fostering sustainable environmental innovation.Conclusions: Integrating smart tourism with environmental sustainability is a strategic necessity to enhance resource efficiency and protect the environment, requiring digital infrastructure, updated regulations, and continuous environmental awareness.
Keywords: Smart Tourism; Environmental Sustainability; Artificial Intelligence; Internet of Things; Tourist Destinations; Environmental Sciences; Engineering Tourism; Smart Mobility